CHARACTERISTICS OF COMMUNITY ADAPTIVE RESILIENCE IN OVERCOMING THE HAZARDS OF FLOOD DISASTER IN KAMPAR REGENCY-INDONESIA - Hermon, Dedi; Adura Tengku Hamzah, Tengku Adeline; Febriandi; Ramadhan, Risky; Putra, Aprizon; Rahmi, Lailatur; Sihaini, Etika; Sari, Nadiya (GEOMATE Journal, 2024)
This research aims to formulate a flood hazard model, a community adaptation resilience model, and a community adaptation model for flood disasters in Kampar Regency, Indonesia. The flood disaster hazard model was analyzed using the Geomorphic Flood Index (GFI), while the characteristics of community adaptation resilience in mitigating flood disaster hazards were analyzed through the Climate and Disaster Resilience Initiative (CDRI). This research showed that the flood-free zone in Kampar Regency covered 715850 ha, the low hazard zone spanned 86357 ha, the medium hazard zone extended across 142821 ha, and the high hazard zone included 88658 ha. Areas with a high risk of flood disasters include the sub-districts of Tapung, Tapung Hulu, TapungHilir, Siak Hulu, Tambang, Kampar Kiri Hilir, and Kampar Kiri. Based on the assessment, the community adaptation resilience in Kampar Regency in facing flood disaster hazards scored 49, indicating that the characteristics of community adaptation still lack adequate resilience.